On two arguments against hedonism - de Lazari-Radek, Katarzyna (Hybris, 2016)
Our common sense seems to regard hedonism as an unworthy theory of value. Two main arguments, resting on our intuitions, are commonly presented against it. The first ridicules hedonism as “a theory fit for pigs”, that is for people who care only about simple physical pleasures. The second seeks to refute hedonism on the assumption that no one would like to live a life that is nothing else but a hedonic reflection of her or his mind. Robert Nozick used this intuition to build his famous “experience machine example”. The purpose of this article is to suggest that the intuitions underlying these arguments, are based on non-rational presuppositions and therefore are not the best ways to confront hedonism.